Student Perceptions of Blended Assessment Approach in The Bachelor of Education Degrees in Mathematics And Science Through Open Distance And E–Learning (Odel) - Alois Matorevhu (International Journal of Trends in Mathematics Education Research, 2019)
Blended assessment approach (BAA) comprising closed book test (CBT) and open book test (OBT) assessment strategies is being used in the Bachelor of Education Degrees in Mathematics and Science ODeL programme offered by a University M in Zimbabwe. Adherents to BAA identify compensating for weaknesses of one strategy by another, as its major strength.  Research studies reveal that if assessment strategies are aligned to assessment objectives the gap between the intended and achieved curricula is reduced. This study was conducted to explore how BAA enhanced congruency between the BED Mathematics and Science ODeL intended and achieved curricula based on the perceptions of in– service teachers in the programme. Interviews, focus group discussions (FDGs) and document analysis were used to gather data.  Qualitative data analysis techniques were used, since they were consistent with the objectives of the study. Findings reveal that giving a compulsory OPT after the CBT ensured that learners concentrated both on areas they had challenges, as well as consolidating what they got correct in the CBT. This tended to broaden and deepen frontiers of knowledge of the in–service teachers in their respective subject areas (Mathematics, Physics, Biology and Chemistry). All the in–service teachers in the study concurred that the learner–centred nature of the BAA approach was effective in achieving curriculum objectives. They (in–service teachers) could not hide their support for the BAA by showing their preparedness to immediately implement it in teaching and learning at their schools. Further studies on the use of formative (continuous) assessment strategies like presentations, question setting, group projects and exhibitions by learners are recommended, to improve the blend of assessment strategies in the BAA.